SMOKE DETECTION DESIGN USING MQ-2 SENSOR AND EXHAUST FAN BASED ON MICROCONTROLLER - Adi Winarno; Widodo Widodo; Rahmat Hanif Darmawan (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2023)
Clean air is a very important requirement for life on earth, especially for humans. Nowadays people are competing to maintain air quality in their environment by using Air Conditioners (AC). The use of air conditioning in the home environment without us knowing that the air we breathe is contaminated with smoke. The smoke in the air-conditioned room cannot escape because the room is always closed. As a result, the smoke content that cannot escape is very dangerous, so a prototype of an indoor smoke detector is made using the Arduino microcontroller and the MQ-2 sensor as a smoke sensor. If smoke is detected by the MQ-2 sensor, Arduino will turn on the bazzer and fan.